Interferon beta-1a-induced depression and suicidal ideation in multiple sclerosis - Marco Aurélio Lana-Peixoto; Antônio Lúcio Teixeira Jr.; Vitor Geraldi Haase (Arquivos de Neuro-Psiquiatria, 2002)
Depression and suicide have been reported in association with multiple sclerosis (MS). Some studies show that interferon beta may increase the depression rate. We report a case of depression and suicidal ideation in coincidence with the start of increased doses of interferon beta-1a and their complete reversal following the drug withdrawal. The patient was a 21-year-old man with MS and no past history of affective disorders who was given interferon beta-1a in the dose of 11 mug three times per week. As a new relapse occurred the dose of interferon beta-1a was increased to 22 mug three times a week. The patient then observed increased worry, irritability and a sense of discouragement as well as recurring suicidal thoughts. His mood was rapidly restored following interferon beta-1a withdrawal. This case suggests that patients with MS may develop depression and suicidal thoughts when treated with high doses of interferon beta-1a.